Group Decision Support System (GDSS) dengan Metode Entropy untuk Menentukan Prioritas Antrian Layanan Rumah Sakit Menggunakan Multiple Channel Model (M/M/s) - Ardy Hidayat; Reza Firsandaya Malik; Siti Nurmaini (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The queuing system service at the hospital has a problem that the service queue is longer than the health service itself. Based on the problem, we need a model that is able to provide a queuing services that are right on the target. In this paper, 10 criteria are used to determine the priority of the queue, namely: Risk Factors for Disease, Cost of Care, Medical Personnel, Medical Equipment, Waiting Time, Distance of Patient Domicile, Age, Gender, Number of patients served in the intended unit and Chairperson’s Decision. These 10 criteria in order to obtain more objective results are combined with Group Decision Making Type 2 (GDM2) and entropy methods to evaluate the queue of the Multiple Channel Model (M / M / s). The number of service counters is very influential on the number of queues and service times. The conclusion is that by doubling the number of service counters will cut 1/2 of the number of people served per time unit on each queue, especially between 8.00 am and 10:00 a.m. Furthermore, based on the assessment of Decision Maker (DM) in the decision-making group, the cost criteria are the most important or critical factors when giving priority services, followed by the leadership decision criteria and disease risk factors. Adding dangerous disease categories in the queuing system can make this system better.